Productivity of common bean in relation to phosphate fertilizer and irrigation in a cerrado soil - Miranda, Leo Nobre de; Azevedo, Juscelino de; Claessen, Jeanne Christine; Gomes, Antonio Carlos (Pesquisa Agropecuaria Brasileira, 2000)
The cultivation of common bean (Phaseolus vulgaris L.) with irrigation in cerrado soils, requires the application of phosphate fertilizers. A field experiment was carried out to study the effect of phosphate and water levels on the common bean grain yield in a clay Dark-Red Latosol. Treatments consisted of three levels of phosphate fertilizer (250, 500 and 1.000 kg ha-1 of P2O5) and two water levels (adequate and restricted), defined according to the water tension in the soil. It was cultivated the common bean cultivar Carioca (four crops) in the dry season, in rotation with corn cultivar BR 201 (five crops) in the rainy season. The common bean grain yield increased with phosphate levels in both water levels, being higher with the higher phosphate level and adequate irrigation. Restricted irrigation promoted a general decreasing in grain yield but with less intensity in the soil with higher phosphate availability. Corn grain yield also increased with the phosphate levels. The phosphate residual effects maintained a good grain production for both crops throughout the various years of cropping.